2002
DOI: 10.1002/jbm.10405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotics on the properties of poly(methylmethacrylate)‐based bone cement

Abstract: The goal of this study was to examine the relationship between gentamicin concentration in Palacos R bone cement (in the mass fraction range of 0-9.4%) and various properties of the cement. The results from the thermal, density, and static compression tests show that gentamicin favors the cement polymerization in its final steps, and forms a diphasic structure with the cement [poly(methylmethacrylate)] matrix. The static compression properties in the dry state are only slightly modified by the presence of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
50
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 16 publications
8
50
0
Order By: Relevance
“…Although there is a lack of consensus regarding experimental designs when considering enhancement of the mechanical properties of bone cement [12], the use of antibiotics at dosages of 4 g or greater has resulted in reduced compression strength [7] and fatigue life [13], with values similar to those obtained for the traditional antibiotic cement in this study (Table 4). Our study showed that bone cement incorporating bacterial cellulose maintains its compression strength and fracture toughness even when loaded with 5 g of antibiotic.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Although there is a lack of consensus regarding experimental designs when considering enhancement of the mechanical properties of bone cement [12], the use of antibiotics at dosages of 4 g or greater has resulted in reduced compression strength [7] and fatigue life [13], with values similar to those obtained for the traditional antibiotic cement in this study (Table 4). Our study showed that bone cement incorporating bacterial cellulose maintains its compression strength and fracture toughness even when loaded with 5 g of antibiotic.…”
Section: Discussionsupporting
confidence: 59%
“…Although increasing the amount of antibiotic incorporated increases the level of its release [7,13], 4 g or greater of antibiotic to 40 g of PMMA powder compromises the compression strength [7,12], fracture toughness [4], and fatigue life [12,13,17] of the material. Therefore, we investigated whether incorporating bacterial cellulose would improve the mechanical strength of bone cement containing 5 g of antibiotics and increase antibiotic release.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each specimen was measured with a precision calliper between 22 and 26 h after setting, and only specimens with a length of 11.9±1 mm and a diameter of 6 mm were used. The specimens were also inspected macroscopically, and those with flaws, such as voids or powder clots, were excluded, as numerous studies have indicated that antibiotic inclusions may propagate fracture in cement [8,11,18]. …”
Section: Methodsmentioning
confidence: 99%